Gender and Labor Law Reform in Indonesia: Challenges to the Protection of Women Workers in the Post-Omnibus Law Era - Maesarani; L. ya Esty Pratiwi (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study analyzes post-Omnibus Law labor law reform in relation to the legal protection of women workers in Indonesia. The study is grounded in the gap between normative protection and the practical implementation of women workers’ rights within flexible employment relations. The objective of this study is to compare the regulation of women workers’ protection under Law Number 13 of 2003 and Law Number 6 of 2023, and to examine its juridical implications for job security, maternity rights, and gender justice. This study employs a normative legal method through a statute approach and a comparative approach, by analyzing statutory regulations, legal literature, and court decisions related to labor law. The findings indicate that labor reform continues to maintain the normative protection of women workers; however, the expansion of contract-based employment systems and outsourcing potentially weakens substantive protection, particularly for vulnerable women workers. This study underscores the need for gender-responsive labor policies, strengthened supervision, and effective law enforcement to ensure the sustainable protection of women workers. The findings further indicate that labor market flexibility in contemporary Indonesia tends to prioritize investment over the substantive protection of women workers.